2000
DOI: 10.1027//0227-5910.21.2.71
|View full text |Cite
|
Sign up to set email alerts
|

An Exercise in Improving Suicide Reporting in Print Media

Abstract: This study was conducted to support the publication of guidelines for media reporting on suicide. First, quantitative and qualitative aspects of suicide reporting in Swiss print media were surveyed over a time span of 8 months. The results were presented at a national press conference, and written guidelines for suicide reporting were sent out to all newspaper editors. The results of the survey and the guidelines were discussed in a personal meeting with the Editor-in-Chief of the main tabloid. After the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
2
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 16 publications
9
92
2
2
Order By: Relevance
“…That comparison exceeds the scope of this study but could be a question for the future; second, less textual and more visual presentations were observed. Suicide articles had on average about 400 Chinese characters per article; 58% were accompanied by pictorial presentations or illustrations, compared with 14% of the suicide articles in Australian newspapers36 and 8% in Swiss newspapers 37. In comparison, the Hong Kong newspapers had the highest percentage of suicide articles printed with photos, which was close to 90%; third, the headline of suicide articles, which is the most eye-catching and visually arousing position of a news story, was found to carry many important attention-seeking features, including the suicide method used and the alleged problem encountered by the victim, which could heighten an individual's suicidal thoughts 20.…”
Section: Discussionmentioning
confidence: 99%
“…That comparison exceeds the scope of this study but could be a question for the future; second, less textual and more visual presentations were observed. Suicide articles had on average about 400 Chinese characters per article; 58% were accompanied by pictorial presentations or illustrations, compared with 14% of the suicide articles in Australian newspapers36 and 8% in Swiss newspapers 37. In comparison, the Hong Kong newspapers had the highest percentage of suicide articles printed with photos, which was close to 90%; third, the headline of suicide articles, which is the most eye-catching and visually arousing position of a news story, was found to carry many important attention-seeking features, including the suicide method used and the alleged problem encountered by the victim, which could heighten an individual's suicidal thoughts 20.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the substantial research on media influences and the development of several guidelines for the media to follow in presenting suicide story content [61], research on the specific aspects of media stories that facilitate suicide contagion has been markedly limited [48]. Few studies have systematically investigated the specific story elements believed to either facilitate or limit the contagious effects of media accounts of suicide.…”
Section: Content Analytic Studiesmentioning
confidence: 98%
“…Their content analysis revealed that while the prominence (frequency and placement) of suicide reporting rose, the national suicide rate did not increase. Those few studies that evaluated the qualitative characteristics of newspaper stories [43,48,50,51] either examined a limited number of newspaper articles or appraised a restricted number of newspaper dimensions. The reliability of the newspaper content analyses has only been minimally addressed [43,48,51].…”
Section: Content Analytic Studiesmentioning
confidence: 99%
“…Some limited evidence exists of this. In an initiative in Switzerland it was shown that collaboration between researchers and the media resulted in a reduction of sensational and lengthy reports of suicides in newspapers 11. No attempt was made, however, to measure the impact on suicide.…”
mentioning
confidence: 99%